Transformation of Feature Selectivity From Membrane Potential to Spikes in the Mouse Superior Colliculus - Shi, Xuefeng; Jin, Yanjiao; Cang, Jianhua (Frontiers in Cellular Neuroscience, 2018)
Neurons in the visual system display varying degrees of selectivity for stimulus features such as orientation and direction. Such feature selectivity is generated and processed by intricate circuit and synaptic mechanisms. A key factor in this process is the input-output transformation from membrane potential (Vm) to spikes in individual neurons. Here, we use in vivo whole-cell recording to study Vm-to-spike transformation of feature selectivity in the superficial, visual, neurons of the mouse superior colliculus (SC). As expected from the spike threshold effect, direction and orientation selectivity increase from Vm to spike responses. The degree of this increase is highly variable, and interestingly, it is correlated with the receptive field size of the recorded neurons. We find that the relationships between Vm and spike rate and between Vm dynamics and spike initiation are also correlated with receptive field size, which likely contribute to the observed input-output transformation of feature selectivity. Together, our findings provide useful information for understanding information processing and visual transformation in the mouse SC.